THE ASSOCIATION OF NUTRITIONAL STATUS WITH PSYCHOLOGICAL DISTRESS AMONG CANCER PATIENT IN HOSPITAL UNIVERSITI SAINS MALAYSIA - SHAMSUDIN, JULIANA; LEE MEI LING (International Journal of Allied Health Sciences, 2020)
Malnutrition in cancer patients is common and is always related to psychological distress due to the disease and the treatment process. The aim of this study is to determine whether the nutritional status of cancer patients at Hospital Universiti Sains Malaysia is associated with psychological distress. The study included a total of 102 participants by means of purposive sampling. The information was obtained from medical records on the sociodemographic and clinical data. The weight and height were measured, and the BMI calculation was carried out. The nutritional status was determined using the Patient-Generated Subjective Global Assessment (PG-SGA) and psychological distress was measured using the Depression, Anxiety and Stress Scale-21 (DASS-21). The study group included 53.9% females and 46.1% males (mean age: 55 ± 25 years). Colorectal cancer (21.6%) followed by breast cancer (20.6%) and lymphoma (13.7%) were the most common types of cancer. In PG-SGA 50.0% of the participants suffered from malnutrition (41.2% moderately, 8.8% severe) and 50.0% were well-nourished. Overall, depression, anxiety and stress were 6.9%, 31.4% and 15.7% respectively. The analysis indicated that nutritional status significantly affect the depression score H(2)=11.73, P=0.003, anxiety score H(2)=19.51, P<0.001 and stress score H(2)=9.40, P=0.009. Bonferroni test was further used to compare all pair of groups. There was a significant difference for depression score in Stage A and C (P=0.003), all pair had significant difference for anxiety; Stage A with Stage B (P=0.026), Stage A and C (P<0.001), Stage B and C (P=0.032) and for stress score had significant difference for Stage A and C (P=0.024) only. To conclude, the psychological score was lower in Stage A (well-nourished) than Stage C (malnourished). Our findings suggest the need for more study to clarify the association between nutritional status and psychological distress and ascertain suitable screening and management strategies.